Answer:
a = -1 , b = 4 , c = 3 , d = 1
Explanation:
The general rules of exponent:
![1) \ a^m * a^n = a^(m+n)\\2) \ a^m / a^n = a^(m-n)\\3) (-1)^m = 1 \ (if \ m \ is \ +) and \ = \ -1 \ (if \ m \ is \ -)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/b9s6n8t05sz5f48j4l1pbcs3ci9vcggfj9.png)
===================================================
Given:
![(-xy)^3 (xz) =ax^by^cz^d](https://img.qammunity.org/2021/formulas/mathematics/middle-school/sjagoj0o8yp3euvni6wnalihhdmp21lugp.png)
The right hand side = (-xy)³ (xz) = (-1)³ x³ y³ x z = (-1) x⁴ y³ z
Comparing the right hand side with the left hand side
∴ a = -1
∴ b = 4
∴ c = 3
∴ d = 1